2013
DOI: 10.1182/blood-2012-06-438481
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of viral-vectored vaccines by B cells represents a novel strategy to accelerate CD8+ T-cell recall responses

Abstract: • Using B cells to target antigens into the follicular regions represents a novel approach to accelerate CD81 T-cell recall responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
1
31
1
Order By: Relevance
“…Our in vitro analysis confirmed that infected B cells could transfer Ag to DCs without involving direct contact between the two cells although the exact form of the Ag remains to be determined. It was previously reported that B cells could carry viruses including VSV on their surface and transfer them to other cells (41,42), but our results argue that the Ag is likely in a different soluble form.…”
Section: Discussioncontrasting
confidence: 61%
“…Our in vitro analysis confirmed that infected B cells could transfer Ag to DCs without involving direct contact between the two cells although the exact form of the Ag remains to be determined. It was previously reported that B cells could carry viruses including VSV on their surface and transfer them to other cells (41,42), but our results argue that the Ag is likely in a different soluble form.…”
Section: Discussioncontrasting
confidence: 61%
“…A unique study with oncolytic vaccines addressed this issue by delivering oncolytic vaccines with B cells. Here, the immunodominant gp33 peptide derived from lymphocytic choriomeningitis virus was expressed in three different viruses VSV, Ad, and VV to demonstrate that B cells loaded with the booster virus can elicit better antigen-specific secondary T cell responses, which were dependent on antigen presentation by dendritic cells (62). …”
Section: Heterologous Virus Prime-boost Strategiesmentioning
confidence: 99%
“…By means of an oncolytic rhabdovirus engineered to express TAA and using a prime-boost tumor vaccination approach, it was determined that TAA specific T-cell immune responses can be generated to protect mice from melanoma tumor challenge and lead to a significant diminution in lung metastases. Specific in vivo depletion of cytotoxic CD8 + T-cells during the boost vaccination abolished the therapeutic efficacy of the vaccine, highlighting their mediating role [7981]. …”
Section: Mainmentioning
confidence: 99%